A Study Of Herbal Drugs Utilization Among Pregnant Women, Health Care Professionals, Academicians And Students In Bedong And Sungai Petani - Perveen, Nabila (2017)
This research work attempted to analyze and to evaluate the real values of herbal drugs in aspect of their utilization in pregnant women, health care professionals (physicians)/academicians, and students in specific educational institutions and hospitals in Sungai Petani, Kedah Darul Aman, in Malaysia. Data analysis was performed using Statistical Package of Social Sciences (SPSS), version 20. Total of 1018 respondents were involved in this study consisting of three groups, pregnant women (450), health care professionals (physicians/academicians) (168) and students (400).